ERAS volunteers joined forces with the local community and an NGO in an environment protection programme - Siti Nurfarmy, Ibrahim (2019)
A total of 80 people consisting of staff from Earth Resources & Sustainability Centre (ERAS), Universiti Malaysia Pahang (UMP) students, Sekolah Kebangsaan Bukit Setongkol pupils and members of the Malaysian Nature Society (MNS) took part in a community innovative service programme that was held at a turtle hatchery centre, Rimbun Dahan Turtle Hatchery, in Chendor here on April 10, 2019.